Analyzing the Imagery within The Lyrics of The Album "Monokrom" on "Tulus" Youtube Account and Assessing Its Suitability as an Alternative Teaching Material for Indonesian Language Classes in High Schools - Arindha, Erin; Maruf, Ali Imron Al (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to describe the imagery contained in the lyrics of the album "Monokrom" and describe its relevance as an alternative Indonesian language teaching material in high school using imagery from song lyrics. Album "Monokrom". The research approach used is a qualitative approach with descriptive methods and is included in the type of library study research. The data collection techniques used are listening, reading, listening, and note-taking techniques. The data analysis technique used in this research is interactive and consists of three research components: data reduction, data presentation, and conclusions. Based on the data analysis results, The research found the use of imagery in the song lyrics on the album "Monokrom". Tulus from five images, including 19 visual images, one auditory image, six auditory images, one tactile image, and one olfactory image. The research results can be used as an alternative Indonesian language teaching material in phase F class XII in high school.